ANALYSIS E-SERVICE QUALITY AND CUSTOMER VALUE TO CUSTOMER LOYALTY THROUGH SATISFACTION AS THE INTERVENING VARIABLE (STUDY TO USER OF GO-JEK APPLICATION IN PONTIANAK) - Admin, PRIADE CHRISTIAN B1024151002 (Jurnal Manajemen Update, 2020)
AbstractThe purpose of this research istoanalize the influence of E-Service Quality and Customer Value to the Customer Loyalty towards Satisfaction as the Intervening Variable (Study to User of GO-JEK Application in Pontianak).The competition in transportation sector is increasingly significant improving nowadays. In transportation business sector is commonly known as a vulnerable business when it comes to the problem of the value and quality or performance of the service given. Moreover transportation sector need to make the customer satisfied and loyal to their businesses. From this point we can see that it is undeniable customer loyalty plays an important factor in every industry, especially in transportations sector. While Electronic Service Quality dimensions and Customer Value dimensions are used as the strategy to achieve the Customer Loyalty as they felt satisfied firstly. The data obtained in this research by distributing the online questionnaires and the data is analyze Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software.The hypothesis of the research are.The result of this research shows that H1. H2, H3, H4, H5, H6 are accepted.ReferenceAbraham, M. R. (2009). Importance of a Theoritical Framework for Research.Nuts and Bolts of Chemical Education Research, 976: 47-66.Alreck, P., & Settle, R. (2003).Survey Research Handbook (3rd ed).Newyork: Mcgraw-Hill Education.Cohen, J., P, C., West, S. G., & Aiken, L. S. (2003).Applied Multiple Regression/Correlation analysis in the behavioral sciences (3rd ed).Mahwa, NJ: Erlbaum. p. 76.Cooper, D. R., & Schindler, P. S. (2014).Business Research Methods.Newyork: McGraw-Hill/Irwin.Haemoon Oh, K. K. (2017). Customer Satisfaction, Service Quality, and Customer Value: years 2000-2015.International Journal of Contemporary Hospitality Management, 20-21.Hair, J., & Celsi, M. (2011).Essentials of Business Reseach Methods.Newyork: M.E Sharpe.Hansemark, O. C., & Albinsson, M. (2004). Customer Satisfaction and Retention: The Experiences of Individual Employees Managing Service Quality. 14 (1), pp. 40-57.Jamie Carlson, A. O. (2010). Exploring the Relationship Between E-Service Quality, Satisfaction, Attitudes and Behaviours in Content Driven in Service Website.Jurnal of Service Marketing, 112-127.J.J, H., & Bechger, T. (2011). An Introduction tp Structural Equation Modelling.Family Science Review, 11, 354-373.Kalla, S. (2011). Relationship Between variables Online.Available at: https://exploreable.com/relationship-between-variables, Accessed on 19 January 2019.Kennedy. (2008). The importance of good sampling [Online].available at: http://www.coronainsights.com/2008/08/the-importance-of-good-sampling/, Accessed on 21 January 2019.Khadka, K. &. (2017). Customer Satisfaction and Customer Loyalty.Journal from Centria University of Applied Sciences of Pietaarsari, 9.Kotler, P., & Armstrong, G. (2014).Principles of Marketing (15 ed).Harlow, England: Pearson Education Limited.Kotler, P., & Keller, K. L. (2012).Marketing Management (14 ed).Harlow, England: Pearson Education Limited.Lovelock, C., & Wirtz, J. (2014).Service Marketing (7th Ed).London: Pearson Education.Nayat Sanchez-Pi, J. M. (2010). A Multi-Agent Approach for Provisioning of E-Services in U-Commerce Environments.Internet Research, 279-280.Oliver, R. (1997).Satisfaction as Behavioral Perspective on the Customer.Newyork: McGraw-Hill.O'Shaughnessy, J. A., & O'Shaughnessy, N. J. (2003).The Marketing Power of Emotion.Oxford: Oxford University Press.Pine II, J., & Gilmore, J. H. (1998). Welcome to the Experience Economy.Harvard Business Review, 97-98.Piotr, Z. (2004). Technical Analysis as the Representation of Typical Cognitive Biases.International Review of Financial Analysis, 13(2), 217-225.Popham, W. J. (2008).Transformative Assessment.United States: Houghton Mifflin Harcourt.Prasetyo, B., & Jannah, L. M. (2012).Metode Penelitian Kuantitatif (7th ed).Jakarta: Rajagrafindo Persada.Richard Chinomona, G. M. (2014). The Influence of E-Sevice Quality on Customer Perceived Value, Customer Satisfaction and Loyalty in South Africa.Mediterranien Journal of Social Science, 337-339.Sun, H. (2009). The Impact of Customer Value and Internet Shooping Mall on Customer Loyalty and Satisfaction.International Conference on E-Business, 281-283.Sunil Shadev, K. P. (2008). Modelling the Consequences of E-Service Quality.Marketing Intelligence and Planning, 605-620.Tao, F. (2014). Customer Relationship management based on Increasing Customer Satisfaction.International Journal of Business and Social Science, Volume. 5, Issue. 5 ,pp: 256-263.Thomas, B. &. (2013).Anticipate: Knowing what customers need.NeW Jersey: John Wiley & Sons.Vinzi, V. E., Chin, W. W., Henseler, J., & Wang, H. (2010).Handbook of Partial Least Square: Concepts, Methods and Applications.Newyork: Springer Publication.Vinzi, V., W. W., H., & Wang, H. (2010).Handbook of Partial Least Squares: Concepts, Methods, and Apllication.New York: Springer Publishing.Zeitham, M. J. (2015).Service Marketing Integrating Customer Focus Across the Firm.Ohio: McGraw-Hill.Zikmund, W. (2010).Business Research Methods (8th ed).Canada: Cengange Learning.